Impact of calcium on struvite crystal size, shape and purity. - Le Corre, Kristell S.; Valsami-Jones, Eugenia; Hobbs, Phil; Parsons, Simon A. (Elsevier, 2005)
Struvite precipitation occurs spontaneously in wastewater treatment plants under conditions that are influenced by many factors including concentration of , and ions, pH, temperature and mixing energy. These parameters are often difficult to control and as a result struvite generates problems of scale deposits in areas such as pipes and recirculation pumps. At the same time, struvite is considered as a potentially marketable product as an alternative fertiliser. For those two reasons, it has become important to study the principles of struvite precipitation, and to assess the parameters controlling struvite crystallisation. In the present work the influence of ions on the precipitation of struvite was investigated in aqueous solution containing , and ions in a molar ratio 1:2:2 at room temperature and constant pH. Different laboratory experiments have been used to assess the effects of Ca2+ ions on size, shape, and purity of the crystals formed. Tools used include particle size analysis, X-ray diffraction (XRD) and scanning electron microscopy with energy dispersive X-ray analysis (SEM-EDS). The experimental results showed that the presence of calcium in the media can affect significantly struvite crystal growth, and the characteristics of the crystal produced.